Kewenangan "Lebih" PPATK Sebagai Modal Penegak Hukum Money Loundry - Budianto, Agus (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Amandement to the Law on money laundry was based on weakness of law enforcement effectiveness resulting from the unsinergitas  (disharmony)  between  the  law  enforcement agencies.  Does  not  given  the  authority  to  the  conduct investigations  and  inquiries  to  INTRAC,  do  not  reduces  the central role as the leader of INTRAC agent in the eradication of money laundry. Additional powers to the INTRAC as authority 'more' is the INTRAC can request information on the progress of  investigation  and  the  inquiries  by  criminal  investigators  of origin and / or money laundering. The more authority is run for the benefit of: Handling money laundering effective; Preparation typology  and  strategic  analysis  on  money  laundering  and predicate  offenses;  preparation  of  consolidated  progress  in implementing  anti-money  laundering  regime  in  the  context  of accountability, and/or the preparation of a report for a meeting National  Coordinating  Committee  for  the  Prevention  and Suppression  of  Money  Laundering.  The  realization  of  the implementation these activities, INTRAC can be assistance and request  for  discussion  or  presentation,  and  a  criminal investigation of origin and/or money laundering shall fulfill the information  request.  Thus,  there  is  a  relationship  that  is normative complementarity between investigators with INTRAC within  the framework  of  the  creation  of  a  harmonized enforcement of money laundering.